Effect Of Carbon Black Reinforcement On The Mechanical Properties Malaysia Rubber Compound - Rosszainily., Intan Raihan Asni (2019)
Practically, the natural rubber (NR) is reinforced with carbon black (CB) with the purpose of providing extra strength for both raw and vulcanized NR. The aims of this study, first is to investigate the mechanical properties of the Standard Malaysian Rubber with Constant Viscosity 60 (SMR CV-60) and 25 mol % Epoxidized Natural Rubber (ENR 25) compounds, reinforced with different CB loading through mechanical testing. Second is to evaluate the properties of SMR CV-60 and ENR 25 compounds with different CB loading using the nano-scale testing. Third is to determine the optimal and effective CB loadings in both NR compound for future application. Both the SMR CV-60 and ENR 25 were reinforced with 0, 20, 40 and 60 part per hundred (phr) of CB. Four test which are the tensile, compression, microscopic and nanoindentation were conducted according to the ASTM D412, D395, D575, and E2546 to determine the mechanical properties. In tensile test, both NR compounds were stretched up to 450 % of elongation. The results show that the SMR CV-60 and ENR 25 with 60 phr of CB loading exhibit the highest tensile strength and Young’s Modulus values. However, both compounds had become less elastic as compared to other compounds since the specimens broke at 353% and 352% of elongation for SMR CV-60 and ENR 25, respectively. Higher CB loading reduce the elasticity of NR and increase the stiffness, resulting for higher strength and low elongation at break. For the axial compression test, a constant 2kN load with 3 sec holding time was applied on the specimens. Results showed that the deflection decreased and the Young’s Modulus was increased at the increasing CB loadings. The increased of CB loadings enhances the stiffness of NR compound, increased the resistance of NR compounds toward the compressive force, resulting for lower deflection value. The microscopic studies were also done to investigate the surface morphology of both NR. A pack and folded surface was observed on ENR 25 while lumpy surface was observed on SMR CV-60. Nanoindentation test was carried out by using Berkovich tips with a constant load of 2mN at various holding time of 0, 5, 10, 15, and 20 s. Results shows that SMR CV-60 and ENR 25 compounds with 60 phr exhibit the highest hardness, highest elastic modulus, and lowest penetration depth. This study also showed that the nanoindentation properties were slightly affected by holding time where a fluctuated value was recorded at different holding time. This is due to the reduction of creep effect on the unloading curve, which eventually affects the hardness and elastic modulus readings. Based on the results obtained, it was found that the CB loading highly affects the tensile, compression and nanoindentation properties of both NR compounds. The SMR CV-60 shows better mechanical properties without CB loading while ENR shows better mechanical properties with addition of CB. This is due to ENR 25 have better matrix-filler interaction compared to SMR CV. These studies also revealed that the SMR CV-60 and ENR 25 at 60 phr exhibit highest properties in the tensile strength, compression strength, and the nanoindentation hardness. However, both compounds are not recommended for the application under high strain as the tensile test has recorded the lowest elongation at break compared to other compounds.